First-principles supercell calculations of small polarons with proper account for long-range polarization effects. (28th March 2018) - Kokott, Sebastian; Levchenko, Sergey V; Rinke, Patrick; Scheffler, Matthias
Abstract: We present a density functional theory (DFT) based supercell approach for modeling small polarons with proper account for the long-range elastic response of the material. Our analysis of the supercell dependence of the polaron properties (e.g., atomic structure, binding energy, and the polaron level) reveals long-range electrostatic effects and the electron–phonon (el–ph) interaction as the two main contributors. We develop a correction scheme for DFT polaron calculations that significantly reduces the dependence of polaron properties on the DFT exchange-correlation functional and the size of the supercell in the limit of strong el–ph coupling. Using our correction approach, we present accurate all-electron full-potential DFT results for small polarons in rocksalt MgO and rutile TiO2 .